2022
DOI: 10.1186/s13256-022-03672-5
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrovascular accident in a child with precursor B-cell acute lymphoblastic leukemia and coronavirus disease 2019: a case report

Abstract: Background Coronavirus disease 2019 can lead to rare but severe and life-threatening diseases in susceptible high-risk populations, including patients with immunodeficiency. A rare event in this report is stroke following COVID-19 disease in a patient with an immunocompromised background due to leukemia and anti-cancer treatments. Case presentation A 6-year-old iranian girl with precursor B-cell leukemia receiving vincristine therapy presented wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…It is also particularly important that Coronavirus disease 2019 can lead to rare but severe and life-threatening diseases in susceptible high-risk populations, including patients with immunodeficiency. A rare event in this report 19 is stroke following COVID-19 disease in a patient with an immunocompromised background due to leukemia and anti-cancer treatments. Both of our cases with AFBN were accompanied by high fever, disturbance of consciousness, and elevated inflammatory markers.…”
Section: Discussionmentioning
confidence: 84%
“…It is also particularly important that Coronavirus disease 2019 can lead to rare but severe and life-threatening diseases in susceptible high-risk populations, including patients with immunodeficiency. A rare event in this report 19 is stroke following COVID-19 disease in a patient with an immunocompromised background due to leukemia and anti-cancer treatments. Both of our cases with AFBN were accompanied by high fever, disturbance of consciousness, and elevated inflammatory markers.…”
Section: Discussionmentioning
confidence: 84%
“…37 The report of infection and inflammation of the COVID-19 contributing to seizures and cerebrovascular accidents also confirms the role of neuroinflammation in this regard. 38 Suggested to be linked with synaptic function, the mTOR signaling pathway is thought to influence neuronal excitability, leading to epileptogenesis. 39 This finding indicates that the modulation of the mTOR signaling pathway might be an effective intervention in several kinds of epilepsy.…”
Section: Discussionmentioning
confidence: 99%
“…In this systematic review, identified comorbidities include anemia (Appavu et al, 2021;Beslow et al, 2021;Español et al, 2022) hemoglobinopathies (Beslow et al, 2021;Sa et al, 2021), hematologic malignancies (Sánchez-Morales et al, 2021;Whitworth et al, 2021;Karimi et al, 2022), structural cardiovascular anomalies (Khoshnood et al, 2021;Sánchez-Morales et al, 2021), prior infection with varicella (Beslow et al, 2021), systemic and CNS bacterial and tuberculous infections (Essajee et al, 2020;de Marcellus et al, 2021;Fraser et al, 2022).…”
Section: Comorbidity Predisposing To Stroke In Covid-mentioning
confidence: 99%